Current perspectives on fixed-dose ACE inhibitordiuretic combination therapy in the management of arterial hypertension - G. N. Gorokhovskaya; V. L. Yun; A. I. Martynov; Yu. A. Vasyuk; S. V. Moiseenko (Медицинский совет, 2019)
Despite our achievements in modern medicine, arterial hypertension (AH) remains one of the main causes of fatal complications, such as myocardial infarction and acute cerebrovascular accident leading to disability and mortality of patients, including those of working age. The prevalence of hypertension is significantly higher among old and senile age population, however, it has recently tended to increase in young and middle-aged people. Thus, the Russian epidemiological ESSE-RF study, in which representative sample of the Russian population aged 25–64 years were studied, showed that the prevalence of hypertension in individuals of that age group was 44%. It was predicted that the world’s burden of hypertension would increase by 15–20% to approximately 1.5 million people in the year 2015. Due to the high incidence of hypertension and complications associated with hypertension development, further study of pathogenetic mechanisms, development of diagnostic examination methods, prophylactic measures and the search for new treatment options with fixed-dose combination drugs is an important area of modern medicine. This article provides an overview of clinical studies of the components (lisinopril and indapamide) of a rational ACE inhibitor–diuretic combination and a clinical example.